Nutritional analysis of diets searched on the internet and potential health impacts - Ester Gonçalves Quirino; Mariana Ribeiro Costa Portugal (Universidade do Estado do Rio de Janeiro, 2022)
Introduction: Desire to lose weight has been influencing people to search for restrictive diets. The Internet facilitates access to diets focused mainly on weight loss. Objective: This original research work aimed to analyze menus of the most searched diets by internet users. Method: A search with the word "diet" was conducted in Google Trends, and the most searched diets on the internet between September 2019 and September 2020 were selected, as follows: egg diet, USP diet, Dukan diet, and Sirtfood diet. A search for menus of each one of them was performed, as well as analysis of energy content, the corresponding percentage of protein, lipids, carbohydrates, and fiber, calcium, iron, vitamin C, vitamin A, and vitamin E composition, with the help of the Avanutri software. Results: It was possible to verify that most diets are very restrictive regarding daily energy supply (396.6 to 1326.58 kcal), stimulate a great restriction of carbohydrates (except Sirtfood diet phase 1) and high protein consumption (20-45%), which is accompanied by high intake of lipids (14-47%). Concerning micronutrients, menus showed insufficiency in the daily supply of vitamins A (except Dukan phase 2 and USP diet), C (except egg diet and Sirtfood phase 1), D, E, besides calcium (except Dukan phase 2), and iron. Conclusion: Besides potential risks that an imbalanced nutrient composition may cause, diets with a restrictive profile do not lead to the development of healthy eating habits and may result in the development of an obsessive relationship with food. Although initial weight loss may occur, weight loss is not sustained.